Virus tracking technologies and their applications in viral life cycle: research advances and future perspectives - Liu, Di; Pan, Li; Zhai, Huanjie; Qiu, Hua-Ji; Sun, Yuan (Frontiers in Immunology, 2023)
Viruses are simple yet highly pathogenic microorganisms that parasitize within cells and pose serious threats to the health, economic development, and social stability of both humans and animals. Therefore, it is crucial to understand the dynamic mechanism of virus infection in hosts. One effective way to achieve this is through virus tracer technology, which utilizes fluorescence imaging to track the life processes of virus particles in living cells in real-time, providing a comprehensively and detailed spatiotemporal dynamic process and mechanism of virus infection. This paper provides a broad overview of virus tracking technology, including the selection of fluorescent labels and virus labeling components, the development of imaging microscopes, and its applications in various virus research. Additionally, we discuss the possibilities and challenges of its future development, offering theoretical guidance and technical support for effective prevention and control of the viral disease outbreaks and epidemics.